Analisis Nisbah Kerjasama Umkm Dalam Konteks Musyarakah Di Food Court Toserba Yogya Purwakarta - Rachma Frattiwi (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2019)
This research was conducted at the Yogya Purwakarta Toserba Food Court. The problem that occurred at the Yogya Purwakarta Toserba Food Court was that the concept of the collaboration agreement that was carried out tended to be wrong. The purpose of this study was first to determine the cooperation agreement undertaken by the UMKM with the